EFFECT OF EXPOSURE MEDIA, ENVIRONMENTAL PERFORMANCE AND INDUSTRIAL TYPE ON CARBON EMISSION DISCLOSURE - Fenny Novia Aulia Ulfa; Husnah Nur Laela Ermaya (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
AbstractThe purpose of this research is to test the influence of Media Exposure, Environmental Performance And Type of Industry to Carbon Emission Disclosure. The independent variable in this research is Media Exposure measured using dummy variables, Environmental Performance is measured using an ordinal And Type of Industry is measured using dummy variables. Carbon Emission Disclosure as the dependent variable is measured using a checklist that was adopted from research Choi et al.  The population of this research is non-financial companies that listed in the year 2014-2016. By using purposive sampling method and obtained a total sample of 36 companies per year. Methods of analysis of this research include statistic descriptive analysis, test classic assumptions, hypothesis testing and multiple linear. Results from this study indicate that Media Exposure significantly influences to the extent of carbon emission disclosure. Meanwhile, Environmental Performance and Type of Industry had no significant influence on the extent of carbon emission disclosure. Variable Carbon Emission Disclosure can be explained by the variable Media Exposure, environmental performance and the type of Industry amounted to 30%, while the remaining 70% is influenced by the other variables which are not researched in the study.Keyword: Carbon Emission Disclosure, Voluntary Disclosure, Media Exposure, Environmental Performance, Type of Industry